PENDERAAN DAN PENGABAIAN WARGA EMAS: KAJIAN MENURUT UNDANG-UNDANG DI MALAYSIA: Issues of Abuse and Negligence of Senior Citizens: A Study According to The Law in Malaysia - Samudin, Siti Aisyah; Abu Bakar, Adriana (Journal of Shariah Law Research, 2023)
Golden-agers are often referred to as elderly or veterans who have reached old age. In Malaysia, the use of the term ‘elderly’ refers to a person who has lived long, is old, or is getting old. Cases of elder abuse and neglect are considered to be an increasing concern, with older adults being denied adequate food and care, neglected, or left in hospitals and care. Issues and news stories about abuse are frequently published in newspapers and on social media. The situation is further complicated when it turns out that the perpetrators of this immoral act are usually family members such as children, sons-in-law, or grandchildren. Unlike the issue of child abuse, which often receives immediate attention from the media and society, the issue of elder abuse is often an isolated problem and is rarely reported to the authorities, so older people should be treated appropriately with access to adequate protection and support. Therefore, this article focuses on the issue of elder abuse and neglect through an analysis of the effectiveness of protection for older people involved in cases of abuse and neglect. The data obtained by the documentation method was then analyzed using content analysis and descriptive analysis methods. The results of this study show that existing laws in Malaysia are still insufficient to adequately protect the elderly. As such, some proposals for improving the welfare system for older persons, including government, private sector and community efforts to address and adequately address the problem of elder abuse and neglect are proposed.